Pelatihan Pengelolaan Implementasi Kurikulum Merdeka Di PAUD Kabupaten Sumbawa - Baik Nilawati Astini; Gunawan Gunawan; Nurhasanah Nurhasanah; Ika Rachmayani; I Nyoman Suarta (Indonesian Journal of Education and Community Services, 2024)
The Merdeka Curriculum has become a central focus in Indonesia's educational reform, including in Early Childhood Education (ECE). However, its implementation requires specific understanding and skills from ECE educators. This training aimed to enhance the understanding and skills of ECE teachers in Sumbawa Regency in managing and implementing the Merdeka Curriculum. The method employed was a training program involving 45 ECE teachers from three sub-districts: Buer, Alas, and Alas Barat. The training covered materials on the Merdeka Curriculum concept, learning tool development, and implementation strategies. The results showed an increase in ECE teachers' understanding and skills in managing the Merdeka Curriculum, as reflected in the participants' positive responses and their improved comprehension. The active participation of the participants during the training also demonstrated their enthusiasm and motivation in implementing the Merdeka Curriculum in their respective institutions. It is recommended to conduct further training and provide continuous mentoring to ensure optimal implementation of the Merdeka Curriculum in ECE in Sumbawa Regency.